2013
DOI: 10.1016/j.homp.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Basic research in homeopathy and ultra-high dilutions: what progress is being made?

Abstract: This report summarises the latest research developments in the field of high dilutions and homeopathy, as presented at the GIRI symposium of the leading international organisation of scientists in this field, in Florence, Italy in September 2012. The scientific community's early scepticism concerning the possible biological and pharmacological activity of highly diluted solutions, is giving way to a more open-minded attitude that no longer obstructs critical and experimental investigations in this emerging fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The effect is said to increase with increasing dilutions (Molski 2011), which is the main controversy to the conventional medicines. Although homeopathy meets great scepticism (Ernst 2010), it is increasingly used in western countries (Betti et al 2013). Placebo-controlled trials have shown that there is weak evidence for a specific effect of homoeopathic medicines (Shang et al 2005).…”
Section: Background On Homeopathymentioning
confidence: 99%
“…The effect is said to increase with increasing dilutions (Molski 2011), which is the main controversy to the conventional medicines. Although homeopathy meets great scepticism (Ernst 2010), it is increasingly used in western countries (Betti et al 2013). Placebo-controlled trials have shown that there is weak evidence for a specific effect of homoeopathic medicines (Shang et al 2005).…”
Section: Background On Homeopathymentioning
confidence: 99%
“…Similia principle is plausible and rationale in several fields of medical science. Gelsemium alkaloids are neurotoxic at high doses and therapeutic at low doses (32)(33)(34) Hypothesis on the mechanism of action Gelsemium s. dilutions affect neurosteroid biosynthesis and modulate gene expression in neuronal cells (16,29,35) because it deals with the difficult-to-solve technical issues of high dilutions, hormesis and paradoxical reversal of the effects of drugs. One would therefore expect the related questions to be addressed not through subjective opinions and jeering, but rather on the experiential ground, through patient and critical comparison of data and results.…”
Section: Plausibilitymentioning
confidence: 99%
“…With the advent of nanoparticle formulations gaining importance as effective treatment options, parallels have been drawn between the mechanism of action of nanomedicines and homeopathy. 4 Chikramane et al investigated 30C and 200C homeopathic dilutions of Aurum met and Cuprum met and proved using transmission electron microscopy that these ultra-high potencies contained nanoparticles, which might account for their biological effects. 5 The second leading cause of cancer-related mortality in women is attributed to breast cancer, causing 458,000 deaths annually worldwide.…”
Section: Introductionmentioning
confidence: 99%